Diseño del laboratorio de interpretación turística para la carrera de ingeniería en ecoturismo de la ua-caren de la Universidad Técnica de Cotopaxi - Cayancela Llugsha, David Gustavo (2014)
This project provides essential parameters to implement a Tourist Interpretation Laboratory for Engineering in Ecotourism Career in the Academic Unit of Agricultural Sciences and Natural Resources (UA- CAREN) Technical University of Cotopaxi, which contributes to the process of learning, this one was raised according to the reality and the institution needs. The research has three chapters: The first chapter consists of a literature review, which formulates the same currents and theoretical concepts that are taken into account throughout the process of developing the project, the situational diagnosis with its own strengths, weaknesses, opportunities, threats (FODA) analysis that identifies where UA- CAREN has adequated benefits for the development of research, market survey collects both current and historical information relating to the application within the institution and also by measuring the degree of acceptance where 100% of respondents agree with the implementation of the laboratory, also are stablished communication strategies and advertising which allows to the university community and others become aware of the existence of the services offered by the touristic interpretation laboratory….